Interpreting the pathogenicity of Joubert syndrome missense variants in Caenorhabditis elegans - Karen I. Lange; Sofia Tsiropoulou; Katarzyna Kucharska; Oliver E. Blacque (The Company of Biologists, 2021)
Ciliopathies are inherited disorders caused by defects in motile and non-motile (primary) cilia. Ciliopathy syndromes and associated gene variants are often highly pleiotropic and represent exemplars for interrogating genotype-phenotype correlations. Towards understanding disease mechanisms in the context of ciliopathy mutations, we have used a leading model organism for cilia and ciliopathy research, Caenorhabditis elegans, together with gene editing, to characterise two missense variants (P74S and G155S) in mksr-2/B9D2 associated with Joubert syndrome (JBTS). B9D2 functions within the Meckel syndrome (MKS) module at the ciliary base transition zone (TZ) compartment and regulates the molecular composition and sensory/signalling functions of the cilium. Quantitative assays of cilium/TZ structure and function, together with knock-in reporters, confirm that both variant alleles are pathogenic in worms. G155S causes a more severe overall phenotype and disrupts endogenous MKSR-2 organisation at the TZ. Recapitulation of the patient biallelic genotype shows that compound heterozygous worms phenocopy worms homozygous for P74S. The P74S and G155S alleles also reveal evidence of a very close functional association between the B9D2-associated B9 complex and MKS-2/TMEM216. Together, these data establish C. elegans as a model for interpreting JBTS mutations and provide further insight into MKS module organisation. This article has an associated First Person interview with the first author of the paper.